Risk factors accounting for anal incontinence during the first year after vaginal delivery—A case control study in China - Jia, Yang; Liu, Qingao; Zeng, Lin; Wang, Yan (Frontiers in Medicine, 2023)
Introduction and hypothesis Anal incontinence (AI) is a prevalent postpartum disorder. This study aims to investigate and quantify the risk factors for AI in the Chinese population during the first year following vaginal delivery. Methods The case control study was conducted at Peking University Third Hospital, including all women who delivered vaginally between January 1, 2014, and June 30, 2018. Participants were followed up by telephone interviews 1 year after delivery. AI was defined as the involuntary loss of flatus or feces using a retrospective Jorge and Wexner score above 0. Clinical data were retrieved from the medical record system. Univariate and multivariate analyses were applied to identify potential risk factors accounting for AI. Based on the logistic regression model, a nomogram was constructed to predict the probability of AI postpartum. Restricted cubic spline was utilized to explore potential non-linear relationships between birth weight and AI postpartum. Results Among the 140 AI and 421 none AI cases, we observed antepartum factors like every 100 g of birth weight gain (OR 1.39, 95% CI 1.30–1.49), while intrapartum factors like forceps-assisted vaginal delivery (OR 7.11, 95% CI 2.60–19.45), midline episiotomy (OR 13.11, 95% CI 1.71–100.89), second-degree perineal tear (OR 6.51, 95% CI 1.16–36.68), and third to fourth-degree perineal tear were independent risk factors for postpartum AI. Significantly, infant weighing over 3,400 g at birth increased the risk of AI postpartum. Based on logistic regression model, we constructed a nomogram to estimate the risk of AI 1 year after vaginal delivery. Conclusion Our findings indicated that during the first year following vaginal delivery, infant with birth weight of 3,400 g or more, forceps-assisted vaginal delivery, midline episiotomy, and second to fourth-degree perineal tear increased the risk of AI. As a result, it is essential to limit the routine use of forceps and midline episiotomy and to monitor fetal weight during prenatal care.